Emergence of swine influenza A virus, porcine respirovirus 1 and swine orthopneumovirus in porcine respiratory disease in Germany - Annika Graaf-Rau; Christin Hennig; Kathrin Lillie-Jaschniski; Monika Koechling; Julia Stadler; Jan Boehmer; Ulrike Ripp; Anne Pohlmann; Bernd-Andreas Schwarz; Martin Beer; Timm Harder (Emerging Microbes and Infections, 2023)
Respiratory disease is a significant economic issue in pig farming, with a complex aetiology that includes swine influenza A viruses (swIAV), which are common in European domestic pig populations. The most recent human influenza pandemic in 2009 showed swIAV’s zoonotic potential. Monitoring pathogens and disease control are critical from a preventive standpoint, and are based on quick, sensitive, and specific diagnostic assays capable of detecting and distinguishing currently circulating swIAV in clinical samples. For passive surveillance, a set of multiplex quantitative reverse transcription real-time PCRs (mRT-qPCR) and MinION-directed sequencing was updated and deployed. Several lineages and genotypes of swIAV were shown to be dynamically developing, including novel reassortants between human pandemic H1N1 and the avian-derived H1 lineage of swIAV. Despite this, nearly 70% (842/1216) of individual samples from pigs with respiratory symptoms were swIAV-negative, hinting to different aetiologies. The complex and synergistic interactions of swIAV infections with other viral and bacterial infectious agents contribute to the aggravation of pig respiratory diseases. Using a newly developed mRT-qPCR for the combined detection of swIAV and the recently described porcine respirovirus 1 (PRV1) and swine orthopneumovirus (SOV) widespread co-circulation of PRV1 (19.6%, 238/1216 samples) and SOV (14.2%, 173/1216 samples) was evident. Because of the high incidence of PRV1 and SOV infections in pigs with respiratory disease, these viruses may emerge as new allies in the porcine respiratory disease syndrome.